Partial revision of Japanese Pectinariidae (Annelida: Polychaeta), including redescriptions of poorly known species - Nishi, Eijiroh; Matsuo, Kanako; Kazama-Wakabayashi, Maki; Mori, Atsushi; Tomioka, Shinri; Kajihara, Hiroshi; Hamaguchi, Masami; Kajihara, Naoto; Hutchings, Pat (Zootaxa, 2014)
Eight species of Pectinariidae de Quatrefages, 1866 were recorded from Japan and adjacent waters. We studied four species of the family and redescribe the poorly known species from the Seto Inland Sea and Ariake Sound, Kyushu based on recently collected material. The species covered in this study are Amphictene japonica (Nilsson, 1928), Lagis bocki (Hessle, 1917), Pectinaria okudai (Imajima & Hartman, 1964) and Pectinaria hiuchiensis Kitamori, 1965.